2022
DOI: 10.3389/fmars.2022.917985
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of temperature control on mesopelagic fish and zooplankton communities at high latitudes

Abstract: Across temperate and equatorial oceans, a diverse community of fish and zooplankton occupies the mesopelagic zone, where they are detectable as sound-scattering layers. At high latitudes, extreme day-night light cycles may limit the range of some species, while at lower latitudes communities are structured by dynamic ocean processes, such as temperature. Using acoustic and oceanographic measurements, we demonstrate that latitudinal changes in mesopelagic communities align with polar boundaries defined by deep … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…The strong difference between the SAZ and PFZ observed during this study, both in terms of integrated NASC, and vertical distribution of backscattering at two frequencies, was corroborated by the historical data from the IMOS database at three frequencies, that consistently showed less acoustic backscatter in the PFZ compared to the SAZ (Figure 5). This was also demonstrated in other studies that reported a general decrease in acoustic backscatter with increased latitude (Chawarski et al., 2022; Dornan et al., 2019; Escobar‐Flores et al., 2018, 2020). These changes in acoustic backscatter were not always correlated to changes in fish biomass.…”
Section: Discussionsupporting
confidence: 82%
“…The strong difference between the SAZ and PFZ observed during this study, both in terms of integrated NASC, and vertical distribution of backscattering at two frequencies, was corroborated by the historical data from the IMOS database at three frequencies, that consistently showed less acoustic backscatter in the PFZ compared to the SAZ (Figure 5). This was also demonstrated in other studies that reported a general decrease in acoustic backscatter with increased latitude (Chawarski et al., 2022; Dornan et al., 2019; Escobar‐Flores et al., 2018, 2020). These changes in acoustic backscatter were not always correlated to changes in fish biomass.…”
Section: Discussionsupporting
confidence: 82%
“…The central Nansen Basin. Backscatter declines strongly in the upper mesopelagic zone when crossing boundaries between subpolar and polar water masses 59 , and such a decline was also evident when moving from the near-slope (NB1) to the central (NB2) Nansen Basin (Figs. 2 and 4a, b).…”
Section: Discussionmentioning
confidence: 97%
“…Changing both vertical distribution and directions may confuse predators (Christiansen et al 2022). Success in exploiting resources in the twilight zone would affect possible constraints by photoperiod imposed at high latitudes, with bearing for questions like whether or not the constancy of light regime under climate change will prevent mesopelagic fishes from invading the Arctic (Kaartvedt 2008; Proud et al 2017; Ljungström et al 2021; Chawarski et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic models using B. glaciale to assess climate effects on vertically migrating mesopelagic fishes at high latitudes concluded that their poleward distribution is constrained since foraging fishes would be exposed to visual predators in sunlit upper waters at night also (Ljungström et al 2021; Langbehn et al 2022). On the other hand, Proud et al (2017) suggest that mesopelagic fishes will move poleward as the oceans warm, and Chawarski et al (2022) provided evidence that low temperatures define the biogeographic boundaries of mesopelagic fishes at high latitudes.…”
mentioning
confidence: 99%